Novel approach for quality assessment and improving diagnostic accuracy in cell-based infection imaging using 99mTc-HMPAO labeled leukocytes - Migliari, Silvia; Sammartano, Antonino; Cidda, Carla; Baldari, Giorgio; Scarlattei, Maura; Serreli, Giulio; Ghetti, Caterina; Pipitone, Silvia; Lippi, Giuseppe; Ruffini, Livia (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: Labeled leukocytes with 99mTc-HMPAO are routinely used for infection imaging. Although cell labeling with 99mTc-HMPAO represents an imaging probe to detect infection sites, the diagnostic efficiency of the probe is largely influenced by cell manipulation, multidisciplinary interventions (i.e., biologist, technicians) and available technology (i.e., SPECT, SPECT/CT). The aim of the study was to assess in vitro and in vivo accuracy of a comprehensive approach for quality assessment (QA) of all steps of the procedure. Methods: Radiochemical purity (RCP), pH, labeling efficiency (LE) were measured in 320 procedures. White Cell Viability Factor (WVF) was determined in consecutive blood samples. Images (490 studies) were scored using a 5-point scale. Training program was evaluated using a Learning Questionnaire and a score system. Results: Pre/post-labelling WVF was 0.99% (max value 1%) in all blood samples. LE (mean value 72%) and RCP (>80% until 55 minutes) yielded considerably high values. The vast majority of images were scored as diagnostic by three independent observer (90% with score ≥4). Conclusions: This method appears highly reproducible and easy to use in clinical routine for leukocyte labeling, especially when standardized training and total QA system are implemented.